Searching for squeezed particle-antiparticle correlations in high-energy heavy-ion collisions - Padula, Sandra S. [UNESP]; Socolowski, O. (American Physical Society (APS), 2010)
Squeezed correlations of particle-antiparticle pairs were predicted to exist if the hadron masses were modified in the hot and dense medium formed in high-energy heavy-ion collisions. Although well-established theoretically, they have not yet been observed experimentally. We suggest here a clear method to search for such a signal by analyzing the squeezed correlation functions in terms of measurable quantities. We illustrate this suggestion for simulated pairs at the Relativistic Heavy Ion Collider (RHIC) energies. © 2010 The American Physical Society.